2014
DOI: 10.3400/avd.oa.14-00063
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Wave Velocity Involving Proximal Portions of the Aorta Correlates with the Degree of Aortic Dilatation at the Sinuses of Valsalva in Ascending Thoracic Aortic Aneurysms

Abstract: Objective: To determine the relationship between arterial stiffness measured in different aortic segments and the presence and extent of ascending thoracic aortic aneurysm (ATAA). Methods: Patients at a Thoracic Aortic Diseases clinic at a University teaching hospital were compared to patients attending a Cardiology outpatient Clinic at the same institution. A non-invasive measure of vascular stiffness was performed using pulse wave velocity (PWV) measurement of several vascular segments-carotidfemoral pulse w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Although no correlations were found between aortic root diameters and the stiffness parameters, PWV, and central systolic blood pressure, in this study, it can be speculated that the pulse wave is already altered in its development because the pulse wave arises precisely at the aortic root. At least there is evidence that pulse wave is altered when aortic size is larger at the level of the sinuses of Valsalva [26]. Vriz and co-workers [27] also found that the increment in aortic diameter with age was less when adjusted for aortic stiffness and therefore also recommend taking aortic stiffness measures into account when the increase of aortic diameter is considered.…”
Section: Discussionmentioning
confidence: 99%
“…Although no correlations were found between aortic root diameters and the stiffness parameters, PWV, and central systolic blood pressure, in this study, it can be speculated that the pulse wave is already altered in its development because the pulse wave arises precisely at the aortic root. At least there is evidence that pulse wave is altered when aortic size is larger at the level of the sinuses of Valsalva [26]. Vriz and co-workers [27] also found that the increment in aortic diameter with age was less when adjusted for aortic stiffness and therefore also recommend taking aortic stiffness measures into account when the increase of aortic diameter is considered.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of elastin may increase blood pressure leading to a further increase in circumferential stress, which creates a further impetus for aortic aneurysm expansion. The relative amounts of changes in arterial wall components – collagen, elastin, glycosaminoglycans, fibrulins, fibronectin, and vascular smooth muscle cells – in the aortic segments that experience these changes, may influence aortic compliance in TAA ( 81 ).…”
Section: Arterial Wall Compositionmentioning
confidence: 99%